Language, Saussure and Wittgenstein : - Harris, Roy (Routledge, 1995)
This book exposed two most important figures in the development of twentieth-century linguistic thought. Each was a revolutionary within his own discipline. Each had far-reaching influence outside his own discipline. Each has given rise, independently, to a large corpus of interpretation, translation, exegesis and criticism